Pendekatan Multi-Stakeholders Dalam Penanganan Overloading - IGW Samsi Gunarta; Idwan Santoso (The Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
Overloading in freight transport has caused great concern to a number of transport authorities in many countries. A number of efforts, including to intensify load enforcement, deploy load permit scheme, and increase penalty for overloading offences, have been taken. Nevertheless, an optimistic outcome has not showed up to deter such offence to the moment. This paper tried to view another approach in tackling overloading by integrating multistakeholders